1996
DOI: 10.2134/agronj1996.00021962008800040021x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Transport in a Temperate Grassland: II. Diurnal Fluctuations in Response to Weather and Management Conditions

Abstract: Ammonia emission into the atmosphere is of concern because of its potential impact on atmospheric aerosol chemistry and fertilizer N use efficiency. The purpose of this study was to evaluate the effects of N surplus and deficit on soil‐plant‐atmosphere NH3 exchange in a temperate humid grassland. Plant and soil N measurements were made along with NH3 fluxes using flux‐gradient techniques. Ammonia flux was related to the plant ammonia compensation point (NH3 CP), which was controlled by plant N concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 15 publications
(33 reference statements)
2
22
1
1
Order By: Relevance
“…Total N removal was determined by the difference in the monthly average mass N load between the inlet and outlet of each wetland cell. The extrapolation of daytime hourly rates to daily rates may have overestimated NH 3 volatilization because volatilization tends to exhibit a diurnal pattern where NH 3 volatilization is lower during the night (Bussink et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Total N removal was determined by the difference in the monthly average mass N load between the inlet and outlet of each wetland cell. The extrapolation of daytime hourly rates to daily rates may have overestimated NH 3 volatilization because volatilization tends to exhibit a diurnal pattern where NH 3 volatilization is lower during the night (Bussink et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Wichink Kruit et al (2007) observed a similarly timed increase that coincided with a decrease in leaf wetness. Furthermore, Flechard et al (1999) and Bussink et al (1996) found that water layers sorbed on leaves can store significant quantities of NH 3 even at an RH below 100 %. Although no leaf wetness sensor was employed during this study, we use nighttime RH as a surrogate for dew and fog formation.…”
Section: Morning Increase Of Nhmentioning
confidence: 99%
“…Several investigations have revealed the bidirectional character of NH 3 exchange between vegetation and the atmosphere with large fluctuations on annual, seasonal and daily time scales (Sutton et al, 1995(Sutton et al, , 2007Bussink et al, 1996;Herrmann et al, 2001;Horvath et al, 2005;Walker et al, 2006). In a non-fertilized managed grassland in The Netherlands, NH 3 emission fluxes were frequent (about 50% of the time) during a warm and dry summer period, while in a wet and cool autumn period deposition fluxes dominated (80% of the time; Kruit et al, 2007).…”
Section: Introductionmentioning
confidence: 99%